How do firms in Argentina get financing to export? - Tomás Castagnino; Laura D'Amato; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2012)
This paper delves into the importance of access to .nancing for the performance of firms in export markets. Based on a unique microeconomic database that combines data on Argentine firms' characteristics and export performance with information on their domestic and external financing, we provide a rich insight into their financing patterns. Through the use of a descriptive and econometric analysis, we find that: i) having more access to bank credit facilitates firms' entry into export markets, ii) once they become exporters, it is the access to foreign financing what seems to matters for their success in foreign markets. Also, to study the duration of firms in export markets, we estimate survival functions by firm size, using the Kalpan-Meier estimator. We find that the probability of firms' survival in export mar kets increases with their size in the earlier years of exporting. Once firms become regular exporters, their permanece in export markets seems to less dependent on their size.
Keywords: F10; F13; G20; G28; 330; credit constraints; bank credit; international trade